2015
DOI: 10.1016/j.chb.2014.11.034
|View full text |Cite
|
Sign up to set email alerts
|

Purpose of social networking use and victimisation: Are there any differences between university students and those not in HE?

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 35 publications
(30 reference statements)
0
21
1
Order By: Relevance
“…This result conflicts with a previous study which argued that the level of education is not significantly related to phishing victimisation [12]. But most importantly, when comparing university students with people from outside higher education institutions [44], both behave in a similar way in social networks. Yet, students have been found to be less likely to fall victim to cyber-attacks.…”
Section: Findings and Discussioncontrasting
confidence: 56%
“…This result conflicts with a previous study which argued that the level of education is not significantly related to phishing victimisation [12]. But most importantly, when comparing university students with people from outside higher education institutions [44], both behave in a similar way in social networks. Yet, students have been found to be less likely to fall victim to cyber-attacks.…”
Section: Findings and Discussioncontrasting
confidence: 56%
“…Thus, users can search for people that are able to provide particular information, help them to find it, or transfer knowledge to other people (Ray, 2014;Schouten, 2011). Facebook, in particular, is a source that is easily accessible and also simple to use, and is often employed by students to ask questions about studies and to study interactively (Benson et al, 2015;Gregory et al, 2014;Hussain, 2012). Highly popular media are also those that enable Internet users to express themselves on a specific topic in the form of the written word, oral expression, taking and collecting photos or recording videos, for example, Twitter, YouTube, Instagram, Pinterest, and also to use the information placed there by other users (Hamid et al, 2015;Munguatosha et al, 2011;Nakagawa and Arzubiaga, 2014;Schouten, 2011;Ward, 2006).…”
Section: Literature Overviewmentioning
confidence: 99%
“…A variety of some other studies have also been reported on the usage of social media to positively support student education and their learning process (Ainin, Naqshbandi, Moghavvemi, & Jaafar, 2015; Al-Rahmi & Zeki, 2016; Junco, Heiberger, & Loken, 2011; Tarantino, McDonough, & Hua, 2013). Social media’s easy accessibility, direct interface, and other convenient capabilities have provided it with a highly deserved place in the current landscape of science and technology (Benson, Saridakis, & Tennakoon, 2015). Besides this, previous studies call for more research to examine how social media is perceived and accepted by students for education and learning purposes (Shittu, Madarsha Basha, & Ahmad, 2011; Raaij & Schepers, 2008), as many issues are still unexamined.…”
Section: Introductionmentioning
confidence: 99%